2012
DOI: 10.1039/c1cc16432e
|View full text |Cite
|
Sign up to set email alerts
|

Robust antimicrobial compounds and polymers derived from natural resin acids

Abstract: We report novel robust resin acid-derived antimicrobial agents that exhibit excellent antimicrobial activities against a broad spectrum of bacteria (6 Gram-positive and 7 Gram-negative) with selective lysis of microbial membranes over mammalian membranes. Our results indicate that hydrophobicity and unique structures of resin acids can be determining factors in dictating the antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(89 citation statements)
references
References 31 publications
1
86
0
Order By: Relevance
“…In addition, Decho and co-workers connected derivatives of resin acids to the poly(ε-caprolactone) as hydrophobic groups (Figure 1b). 35 This kind of polymers, containing resin ring structures, exhibit considerable antimicrobial activities against a broad spectrum of bacteria (MICs: Gram-positive bacteria 0.7-10.1 μM; Gram-negative bacteria 3-40 μM) with high selectivity (HC 50 even higher than 860 μM). From the experiments, they suggested that the great antimicrobial activity was related to the structure of resin acids and hydrophobicity.…”
Section: Monomer Designsmentioning
confidence: 99%
“…In addition, Decho and co-workers connected derivatives of resin acids to the poly(ε-caprolactone) as hydrophobic groups (Figure 1b). 35 This kind of polymers, containing resin ring structures, exhibit considerable antimicrobial activities against a broad spectrum of bacteria (MICs: Gram-positive bacteria 0.7-10.1 μM; Gram-negative bacteria 3-40 μM) with high selectivity (HC 50 even higher than 860 μM). From the experiments, they suggested that the great antimicrobial activity was related to the structure of resin acids and hydrophobicity.…”
Section: Monomer Designsmentioning
confidence: 99%
“…Cellulose is an abundant renewable biopolymer. [39][40][41] DAEMA is a methacrylate-based monomer containing renewable resin acid from rosin, [42][43][44][45][46][47][48][49][50] and LMA is derived from a renewable fatty acid. In our related previous work, we reported the polymerization of DAEMA monomer by ATRP to produce homopolymers and block copolymers with controlled molecular weight and low polydispersity index.…”
Section: -24mentioning
confidence: 99%
“…Chemical studies on P. kesiya var. langbianensis have been conducted, and terpenes have been identified as the major component in resin (Wang et al 2012). When the volatile compounds of resin from P. kesiya were examined, the main constituents of resin discovered were α-pinene, β-pinene, β-phellandrene, 3-camphene, myrcene, longifolene, and caryophyllene (Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%